2020
DOI: 10.3390/biomedicines8120586
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin Exerts Antitumor Effect on Human Hepatocellular Carcinoma Xenografts in Athymic Nude Mice through Inhibiting NF-κβ Pathway

Abstract: Cardamonin (CADMN) exerts an in vitro antiproliferative and apoptotic actions against human hepatocellular carcinoma cells (HepG2). This study aimed to investigate the in vivo anti-tumorigenic action of CADMN against human hepatocellular carcinoma xenografts in an athymic nude mice, as well as to study the molecular docking and safety profile of this compound. Acute toxicity study demonstrated that CADMN is safe and well-tolerated up to 2000 mg/kg in ICR mice. Oral administration of 50 mg/kg/day of CADMN in xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Moreover, we also analyzed ADMET (Absorption, Distribution, Metabolism, Elimination, Toxicity) properties to confirm whether cardamonin could be considered a promising drug candidate. In this sense, an acute toxicity study demonstrated that cardamonin is safe and well‐tolerated up to 2000 mg/kg in mice [34] . Also, the assessment results ( Table 3) showed that cardamonin does not violate any of Lipinski's rule of five [33,34] .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, we also analyzed ADMET (Absorption, Distribution, Metabolism, Elimination, Toxicity) properties to confirm whether cardamonin could be considered a promising drug candidate. In this sense, an acute toxicity study demonstrated that cardamonin is safe and well‐tolerated up to 2000 mg/kg in mice [34] . Also, the assessment results ( Table 3) showed that cardamonin does not violate any of Lipinski's rule of five [33,34] .…”
Section: Resultsmentioning
confidence: 88%
“…In this sense, an acute toxicity study demonstrated that cardamonin is safe and well‐tolerated up to 2000 mg/kg in mice [34] . Also, the assessment results ( Table 3) showed that cardamonin does not violate any of Lipinski's rule of five [33,34] . Considering the Log P values, which may be related to the molecule absorption and should be less than 5, we could suggest that cardamonin has good absorption and oral bioavailability.…”
Section: Resultsmentioning
confidence: 89%
“…Pubchem was used to make sdf format and converted to PDB format using Pymol and further used for docking studies. The starting structures of the proteins were prepared using AutoDock tools [65]. Water molecules were deleted, and polar hydrogen and Kollman charges were added to the protein starting structure.…”
Section: Docking Of Thymoquinonementioning
confidence: 99%
“…The chalcone also has Π–Π bonds with TYR204. The free binding energy of 5-fluorouracil is superior to that of CD, which is explained by the stabilization of the active pocket by two aromatic residues in the structure of the chalcone [ 212 ].…”
Section: Anticancer Activitymentioning
confidence: 99%